Multimodal analysis of genome-wide methylation, copy number aberrations, and end motif signatures enhances detection of early-stage breast cancer - Pham, Thi Mong Quynh; Phan, Thanh Hai; Jasmine, Thanh Xuan; Tran, Thuy Thi Thu; Huynh, Le Anh Khoa; Vo, Thi Loan; Nai, Thi Huong Thoang; Tran, Thuy Trang; Truong, My Hoang; Tran, Ngan Chau; Nguyen, Van Thien Chi; Nguyen, Trong Hieu; et al. (Frontiers in Oncology, 2023)
Breast cancer causes the most cancer-related death in women and is the costliest cancer in the US regarding medical service and prescription drug expenses. Breast cancer screening is recommended by health authorities in the US, but current screening efforts are often compromised by high false positive rates. Liquid biopsy based on circulating tumor DNA (ctDNA) has emerged as a potential approach to screen for cancer. However, the detection of breast cancer, particularly in early stages, is challenging due to the low amount of ctDNA and heterogeneity of molecular subtypes. Here, we employed a multimodal approach, namely Screen for the Presence of Tumor by DNA Methylation and Size (SPOT-MAS), to simultaneously analyze multiple signatures of cell free DNA (cfDNA) in plasma samples of 239 nonmetastatic breast cancer patients and 278 healthy subjects. We identified distinct profiles of genome-wide methylation changes (GWM), copy number alterations (CNA), and 4-nucleotide oligomer (4-mer) end motifs (EM) in cfDNA of breast cancer patients. We further used all three signatures to construct a multi-featured machine learning model and showed that the combination model outperformed base models built from individual features, achieving an AUC of 0.88 (95% CI: 0.84-0.9), a sensitivity of 65% at 91% specificity. Hence, our findings showed that a multimodal liquid biopsy assay based on analysis of cfDNA methylation, CNA and EM could enhance the accuracy for the detection of early-stage breast cancer.